Identification of two distinct subsets of gamma/delta T cells with unique cell surface phenotype and tissue distribution - MacHugh, Niall D.; Mburu, J.K.; Carol, M.J.; Wyatt, C.R.; Orden, J.A.; Davis, W.C. (1997)
We describe the characterization of two subsets of bovine gamma delta T cells having distinct cell surface phenotype and tissue distribution. One population expresses the previously described 215000 MW WC1 antigen and is negative for the cell-surface differentiation antigens CD2. CD4, and CD8. The second population expresses CD2 and CD8 but not WC1 and appears to have a T-cell receptor (TCR) rearrangement distinct from that of the WC1+ population. The WC1- population is found in large numbers in spleen and intestine. In addition. This subset is not recognized by a number of monoclonal antibodies (mAbs) specific for TCR families that are well represented in the WC1+_ population. The results indicate that the gamma delta T-cell population in cattle is considerably larger than previously described and that this population can be subdivided into two distinct subsets based on cell-surface phenotype and tissue distribution.